Determination of the new anthelmintic monepantel and its sulfone metabolite in milk and muscle using a UHPLC-MS/MS and QuEChERS method - Kinsella, Brian; Byrne, P.; Cantwell, H.; McCormack, M.; Furey, A.; Danaher, M. (Elsevier BV, 2011)
This is the first paper to report a method for the detection of the new anthelmintic monepantel and its sulfone metabolite in goat's milk and ovine muscle. Samples were extracted and purified using a modified QuEChERS method. A concentration step was included when analyzing in the low μgkg -1 range. Analysis was carried out by ultra high performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) in a 13min run time using atmospheric pressure electrospray ionisation in the negative mode (ESI - ) and multiple reaction monitoring (MRM) scanning. Monepantel (m/z 472) and monepantel-sulfone (m/z 504) both had product ions at m/z 186 and m/z 166. The method has been single-laboratory validated according to the 2002/657/EC guidelines. The mean recovery in milk was 108 and 106% for monepantel and monepantel-sulfone, respectively. The mean recovery in muscle was 109 and 108% for monepantel and monepantel-sulfone, respectively. The coefficients of variation for the within laboratory repeatability and reproducibility were ≤6.4% in milk and ≤14.2% in muscle. The decision limits (CCα) in milk were 2.20 and 2.08μgkg -1 for monepantel and monepantel-sulfone, respectively. The decision limits (CCα) in muscle were 771 and 746μgkg -1 for monepantel and monepantel-sulfone, respectively. © 2011 Elsevier B.V.